(untitled) (Bangladesh Journal of Agricultural Research, 2010)
Field experiments with French bean comprising two varieties (BARI bush bean-1 and BARI bush bean-2), three plant densities (500 x 103, 333 x 103, and 250 x 103 plants/ha as maintained by 20 x 10, 30 x 10, and 40 x 10 cm spacings, respectively) and three levels of N (0, 60, and 120 kg/ha) were conducted at the Agricultural Research Station, Raikhali in the district of Rangamati during the winter (rabi) seasons of 2004-05 and 2005-06. BARI bush bean-1 outyielded BARI bush bean-2. The lowest plant density (250 x 10 plants/ha) recorded significantly higher values of growth and yield attributes, except plant height which was the maximum with the highest plant density of 500 x 103 plants/ha. The highest plant density of (500 x 103 plants/ha) resulted in the highest pod yield in comparison with the lower and medium plant densities. Application of 120 kg N/ha coupled with the highest plant density (500 x l03 plants/ha) gave the maximum pod yield of 34.3 t/ha and 30.2 t/ha in BARI bush bean-I and BARI bush bean-2, respectively. Key Words: French bean; plant density; nitrogen. DOI: 10.3329/bjar.v34i1.5760 Bangladesh J. Agril. Res. 34(1) : 105-111, March 2009